Motion Simulation of a Path Controlled Vehicle (Hungarian Journal of Industry and Chemistry, 2010)
The dynamical modelling of a path controlled vehicle is analyzed in this paper. In addition to the discussion to determine the orientation and location of a vehicle the problems of redesigning a commercial mini car are also discussed. Special emphasize has been laid on the dynamical analysis of the model in the starting transient period. A simple controlling were also attached to the model The velocity, current flow and the roamed path have been obtained.
Keywords: Path Control; Motion Simulation; Dynamical Analysis; Dynamical Model